Building A Village From The Outside: A Study On The Perception And Quality Of Village Government Apparatus In Management Of Village Funds In Regions, Latest, Outside, Frontest In Moa Sub-District, Southwest Maluku Regency - Rukmuin Wilda Payapo; Linda Grace Loupatty (International Journal of Educational Research & Social Sciences, 2021)
This study aims to determine the perception and quality of village government officials on the management of village funds in the area (Last, Outermost, Frontier) in Moa District, Southwest Maluku Regency. This research was conducted in 7 villages namely; Werwaru Village, Tounwawan Village, Moain Village, Klis Village, Patti Village, Wakarleli Village, and Kaiwatu Village, with a descriptive qualitative approach. The types of data used are primary data and secondary data. Data collection techniques are observation, interviews, and literature review. The results showed that the perception of village government officials in Moa District, Southwest Maluku Regency in managing village funds was more focused on physical development and infrastructure improvement. It should be prioritized for village community empowerment programs to improve the welfare and quality of life of the community as well as poverty alleviation in the (Leading, Outermost, Frontier) areas. Village officials must be able to map the potential and needs of the village clearly so that the priority scale of development and community empowerment is according to the needs of the village community. The quality of village government apparatus in Moa Subdistrict, Southwest Maluku Regency in managing village funds is still very low, thus requiring assistance in managing village finances. Unfortunately, village assistants are sometimes not available, so they are not optimal in assisting. The low capacity of human resources results in a lack of understanding of village government officials regarding the implementation of Law No. 6 of 2014, PP No. 43/2014, and Minister of Home Affairs regulations No. 113/2014. Village government officials do not understand the Village Financial System (Siskeudes), so they are often constrained in reporting and accountability of Village Funds